Partisipasi Perantau; Basamo Mambangun Nagari Di Nagari Sungai Pua Kabupaten Agam - Annisa Aulia Putri (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2019)
Nagari Sungai Pua is one of the nagari located in Sungai Pua District, Agam Regency. Since the Dutch colonial era, the people of Nagari Sungai Pua generally have preferred entrepreneurship in the overseas or outside of the nagari area. Therefore, the emigrants of Nagari Sungai Pua have spread everywhere and have a structured organization called the Family Association of Emigrants of Sungai Pua or Ikatan Keluarga Perantau Sungai Pua (IKPS). Although migrating, the emigrants remain residents of Nagari Sungai Pua who also have an obligation to build Nagari. Development in Nagari Sungai Pua is already quite high. In general, every development activity involves emigrants, especially in terms of funding. One example is the construction of the Wali Nagari Sungai Pua office, where 1.3 billion (65%) of the budget came from non-governmental organizations, while another 700 billion (35%) came from the Nagari Funds Allocation. In addition, the construction of religious facilities in each jorong is also built using emigrants. This study aims to describe the participation of emigrants in development in Nagari Sungai Pua. The research method used was qualitative with the technique of collecting data on interviews with Secretary of Nagari Sungai Pua and documentation. Type of research is descriptive analysis. The conclusion of this study is the participation of emigrants in development in Nagari Sungai Pua high. Based on the development data from 2008 to 2016, the highest percentage of sources of development funding is through community self-help, which is funds collected from emigrants.